Handbook of security and networks - Xiao, Yang; Li, Frank H; Chen, Hui (World Scientific, 2011)
This handbook provides a comprehensive overview of network security principles, technologies, and applications. It covers topics such as cryptography, intrusion detection, wireless security, and secure network protocols. Designed for researchers, practitioners, and students, the book offers both theoretical foundations and practical approaches to protecting modern communication networks.